Diverse by design: literacy education within multicultural institutions - Schroeder, Christopher, author; Utah State University Press, publisher (Colorado State University. Libraries, 2011)
Diversity, despite what we say, disturbs us. In the U.S., we debate linguistic rights, the need for an official language, and educational policies for language minority students. On the one hand, we believe in the rights of individuals, including (at least in the academy) the right to one's own language. On the other hand, we sponsor a single common language, monolingual and standard, for full participation and communication in both the academy and in U.S. society.
pt. 1. The problems -- pt. 2. Everyday experiences at NEIU -- pt. 3. Connections and conclusions.
Keywords: Hispanic Americans -- Education (Higher) -- Case studies; English language -- Study and teaching -- Spanish speakers -- Case studies; Literacy -- Social aspects -- United States -- Case studies; Hispanic Americans -- Ethnic identity -- Case studies